Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\lim _{x \rightarrow 0} x \ln(x)$$

I would say the limit will equal 1+ ln(x) but x cannot equal 0 at this point, so what shall i do ?

share|cite|improve this question
Could you say more about why you think the limit equals 1 + ln(x) (and what you even mean by that)? – mweiss Jul 8 '14 at 2:02
$1+\ln x$ is the derivative of $x\ln x$, but l'Hopital's rule for $\lim f(x)$ has nothing to do with the derivative of $f(x)$. – David Jul 8 '14 at 2:12
Remember that L'Hopital rule applies when you evaluate a limit and the result is an undetermined form ($0/0, \infty/\infty$) – AndrewGSM Jul 8 '14 at 4:16

You need to turn it into something that you can use l'Hopital on - that is, 0/0 or $\infty/\infty$.

For example, $$\frac{\ln(x)}{1/x}$$

share|cite|improve this answer
So does l'Hopital's rule apply? – John Jul 8 '14 at 1:59
Well, what are the limits of the numerator and denominator of that expression as x approaches 0 from the right? – mweiss Jul 8 '14 at 2:01

Let $u=-\ln(x)$ which changes the problem to

$$- \lim_{u\to \infty} \frac{u}{e^u}.$$

Can you see it now?

share|cite|improve this answer

$$\lim _{x \rightarrow 0} x \ln(x)=\lim _{x \rightarrow 0} \frac {\ln(x)}{\frac{1}{x}}=\lim _{x \rightarrow 0} \frac{\frac{1}{x}}{\frac{-1}{x^2}}=-\lim _{x \rightarrow 0}x=0 $$

share|cite|improve this answer

without L'Hopital

$\lim _{x \rightarrow 0} x \ln(x) = \lim_{x \rightarrow 0} \frac{\ln(x)}{1/x}$

then, $ y = 1/x $ and when $x \rightarrow 0$, we know $y \rightarrow \infty$

then our limit is $\lim_{y \rightarrow \infty} \frac{\ln(1/y)}{y} = \lim_{y \rightarrow \infty} \frac{\ln(1)- \ln(y)}{y} = \lim_{y \rightarrow \infty} \frac{- \ln(y)}{y} = \lim_{y \rightarrow \infty} -\frac{1}{y} \ln(y)$

$\lim_{y \rightarrow \infty} -\ln(y ^ \frac{1}{y} )$

And We know $\lim_{y \rightarrow \infty} y ^ \frac{1}{y} = 1 $ , then our limit
$\lim_{y \rightarrow \infty} -\ln(y ^ \frac{1}{y} ) = -\ln(1) = 0$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.